2021
DOI: 10.3389/fgene.2021.661474
|View full text |Cite
|
Sign up to set email alerts
|

A Genetically Informed Longitudinal Study of Loneliness and Dementia Risk in Older Adults

Abstract: Although several studies have shown small longitudinal associations between baseline loneliness and subsequent dementia risk, studies rarely test whether change in loneliness predicts dementia risk. Furthermore, as both increase with advancing age, genetic and environmental selection processes may confound the putative causal association between loneliness and dementia risk. We used a sample of 2,476 individual twins from three longitudinal twin studies of aging in the Swedish Twin Registry to test the hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In LISS, a propensity-score-matched study of loneliness change found that loneliness did not change in this particular sample (Buecker et al, 2021). In Octo-Twin and SATSA, it was found that loneliness follows a U -shaped curve, swinging up after age 60 (Kim et al, 2021; Phillips et al, 2022). In SHARE, late-life loneliness was related to educational and family factors, but loneliness trajectories were not formally tested (Fernández-Carro & Gumà Lao, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…In LISS, a propensity-score-matched study of loneliness change found that loneliness did not change in this particular sample (Buecker et al, 2021). In Octo-Twin and SATSA, it was found that loneliness follows a U -shaped curve, swinging up after age 60 (Kim et al, 2021; Phillips et al, 2022). In SHARE, late-life loneliness was related to educational and family factors, but loneliness trajectories were not formally tested (Fernández-Carro & Gumà Lao, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the initial data collection for the analysis was conducted from 2010–2014, and represents a pre-pandemic experience, however, the levels of loneliness and social isolation reported in the study also vary greatly from the national average at the time. Similarly, a genetically informed longitudinal study also failed to establish a link between loneliness and dementia risk in older adults [ 68 ]. The study comprised of 1,632 pairs of twins from the Swedish Twin Registry who participated in one of the three previous longitudinal studies.…”
Section: Loneliness and Social Isolation As Dementia Risk Factorsmentioning
confidence: 99%
“…There are two hypotheses—the social causation hypothesis states that loneliness itself increases the risk of dementia, whereas under the social selection hypothesis the risk of dementia among lonelier people is more likely to occur because of their greater underlying biological and environmental risk exposure. For instance, in pairs of monozygotic twins, differences in the effect of loneliness on dementia risk should be attributed to the twins’ dissimilarity in environmental exposure, as they share all of their genotypes and common environments [ 20 ].…”
Section: Feeling Lonely Being Alone and Their Connection With Dementiamentioning
confidence: 99%